2016
DOI: 10.1080/09273948.2016.1215475
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Uveitis in a Tertiary Ophthalmology Center in Thailand

Abstract: Herpetic uveitis was the commonest form of infectious uveitis, whereas Vogt-Koyanagi-Harada disease was most frequently seen as the non-infectious cause of uveitis in Thailand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 20 publications
2
11
1
Order By: Relevance
“…Over time, the evolvement and advancement of diagnostic tools and imaging techniques have enhanced the way we diagnose and manage uveitis patients [2]. As the common causes of uveitis vary worldwide, the incidence for certain uveitides may differ according to region [3][4][5][6][7][8][9]. Understanding the epidemiology and causes of uveitis in various regions will further aid clinicians in a targeted approach to managing patients with diagnostically challenging uveitis.…”
Section: Introductionmentioning
confidence: 99%
“…Over time, the evolvement and advancement of diagnostic tools and imaging techniques have enhanced the way we diagnose and manage uveitis patients [2]. As the common causes of uveitis vary worldwide, the incidence for certain uveitides may differ according to region [3][4][5][6][7][8][9]. Understanding the epidemiology and causes of uveitis in various regions will further aid clinicians in a targeted approach to managing patients with diagnostically challenging uveitis.…”
Section: Introductionmentioning
confidence: 99%
“…Gender predilection of VKH disease seems to vary globally. Studies from the Philippines and India have suggested that women are affected more frequently than men, whereas men and women are equally represented in other studies from the Asia-Pacific region [24,25,43,85].…”
Section: Epidemiologymentioning
confidence: 91%
“…Studies in China, Taiwan, and Thailand have revealed relatively consistent patterns of uveitis. Noninfectious uveitis represents 41-55% of cases in China and 38-44% in Thailand [5,6,8,[40][41][42][43]. It also represents the majority of uveitis cases in Taiwan, accounting for 47-83% of etiologies [44][45][46].…”
Section: Epidemiology and Distribution Of Etiologiesmentioning
confidence: 99%
“…This explains the great heterogeneity of the studies reported in the literature. The main etiologies (mostly reported from tertiary centers) are Vogt-Koyanagi-Harada disease (VKH) and sarcoidosis in Japan [7], VKH and Behçet's disease (BD) in China [8], BD in Turkey [9], HLA-B27-associated uveitis in Australia [10], herpesvirus in North Africa [11] and Thailand [12], tuberculosis in India [13], toxoplasmosis in South America [14], and infections (presumed tuberculosis, followed by cytomegalovirus infection and herpesvirus infection) in Singapore [15]. In Western countries, approximately a quarter of cases are related to ophthalmologic entities, a quarter to systemic diseases meeting consensual diagnostic criteria, a quarter to suspected systemic diseases, and a quarter to unexplained causes [16].…”
Section: Introductionmentioning
confidence: 99%